TaxonTableTools: A comprehensive, platform‐independent graphical user interface software to explore and visualise DNA metabarcoding data. (11th March 2021) - Macher, Till‐Hendrik; Beermann, Arne J.; Leese, Florian
Abstract: DNA metabarcoding is increasingly used as a tool to assess biodiversity in research and environmental management. Powerful analysis software exists to process raw data. However, the translation of sequence read data into biological information and downstream analyses may be difficult for end users with limited expertise in bioinformatics. Thus, there is a growing need for easy‐to‐use, graphical user interface (GUI) software to analyse and visualise DNA metabarcoding data. Here, we present TaxonTableTools (TTT), a new platform‐independent GUI that aims to fill this gap by providing simple, reproducible analysis and visualisation workflows. At its base, TTT uses a "TaXon table", which is a data format that can be generated easily within TTT from two input files: a read table and a taxonomy table obtained using various published metabarcoding pipelines. TTT analysis and visualisation modules include Venn diagrams to compare taxon overlap among replicates, samples, or analysis methods. TTT analyses and visualises basic statistics, such as read proportion per taxon, as well as more sophisticated visualisations, such as interactive Krona charts for taxonomic data exploration. Various ecological analyses can be produced directly, including alpha or beta diversity estimates, and rarefaction analysis ordination plots. Metabarcoding data can be converted into formats required for traditional, taxonomy‐based analyses performed by regulatory bioassessment programs. In addition, TTT is able to produce html‐based interactive graphics that can be analysed in any web browser. The software comes with a manual and tutorial, is free and publicly available through GitHub (https://github.com/TillMacher/TaxonTableTools ) or the Python package index (https://pypi.org/project/taxontabletools/ ).